ZEOLITE: STRUCTURE AND POTENTIAL IN AGRICULTURE - Riva Ismawati (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
Zeolite is a hydrated aluminosilicate mineral with a three-dimensional structure. The unique zeolite crystal structure makes zeolites have cation boundary properties, adsorption, molecular sieving, catalysts, capture, and release of air molecules. Many studies in various fields including agriculture have been done by utilizing the properties of the zeolite. Indonesia has an abundant source of zeolite reserves and extensive agricultural areas, making it possible to apply zeolite research results to support sustainable agricultural activities. In this article will discuss the potential utilization of zeolite in agriculture based on the studies that have been done.